Pattern of admission and the over representation in Schizophrenia diagnosis in a psychiatric ward in Malaysia - Mohamad Ismail, Maung Ko @ Hajee; Musa, Ramli; Abu Bakar, Ahmad Zafri; Min Ko, Ba; Mat Zin, Nora; Naing, Nyi Nyi; Oo, Myo (Japan International Cultural Exchange Foundation (JICEF), 2012)
Introduction: Based on the US-UK Diagnostic Project (1972), schizophrenia was over diagnosed at the expense of mood disorders and personality disorders in New York. With the advent of the Diagnostic and Statistical Manual of Mental Disorders (DSM-III), diagnosis of schizophrenia in America became narrow and misdiagnosis of mood disorders as schizophrenia became less. As assessment and reporting of pattern of admission to psychiatric wards is important for strategic service development and planning, this study aimed to investigate the pattern of admissions and identify over representation in schizophrenia diagnosis and under-representation in bipolar mood disorder diagnosis in a psychiatric ward in Malaysia. Method: This was a retrospective record review study of patients with psychiatric illness admitted between 2006 and 2007 in the Psychiatric Ward at Hospital Tengku Ampuan Afzan, Kuantan, Malaysia. Results: Forty-two percent of patients in our study had schizophrenia/delusional disorder and 7.5% had bipolar disorder. Personality disorder had the least number of patients (0.8%). The distribution of schizophrenia diagnosis in our study was higher than the distribution in studies from the West and other Asian countries. It was statistically significant. In contrast, diagnosis of bipolar mood disorder (7.5%) was lower compared with other studies. Conclusions: Our study highlighted the phenomena of over representation in schizophrenia diagnosis and under-representation in diagnosis of bipolar mood disorder. This problem needs to be addressed.